PENGARUH KOMPLEKSITAS AUDIT, TEKANAN ANGGARAN WAKTU, DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT DENGAN VARIABEL MODERATING SISTEM INFORMASI (Studi Empiris pada Kantor Akuntan Publik di Pekanbaru, Medan dan Padang) - Mutiara Jelista; Hardi -; Julita - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of audit complexity, budget pressures of time, and experience of auditors on audit quality by moderating variable understanding of information systems. The population in this study were senior auditors and junior auditors in the firm in Pekanbaru, Medan and Padang, with a total population of 99 auditors. The samples are taken using simple random sampling method, so the number of samples obtained from the calculation formula of determining the total sample of 50 respondents. Primary data collection method used is questionnaire method. Of the 99 questionnaires distributed there are 59 questionnaires returned and used as a sample. The data analysis technique used in this test is multiple regression and regression interactions. Results of hypothesis testing in this study show that, the variable complexity of the audit time budget pressures and experience of auditors variable effect on audit quality. The moderating variable understanding of the interaction of information systems of the variable complexity of the audit time budget pressures and experience of auditors no effect on audit quality.Keywords: Audit, Budget, Auditors, Information Systems and Quality.